Edukasi Manfaat Daun Kelor terhadap Kesehatan - Syukriadi Syukriadi; Muhammad Rizki; Maidayani Maidayani; Yadi Putra; Mansuriza Mansuriza; Ferlita Ferlita (Lembaga Pengembangan Kinerja Dosen, 2025)
Moringa leaves (Moringa oleifera) are known to contain flavonoids that function as natural antioxidants, playing an important role in preventing the oxidation of body cells and maintaining health. However, the results of observations and interviews show that the people of Baet Village still do not understand the health benefits of moringa leaves and how they are processed into food with nutritional value. This community service activity aims to increase public understanding of the health benefits of moringa leaves and skills in processing them into food, vegetables, and various cakes. Partners in this activity are the Kaju Health Center and the people of Baet Village, with a total of 15 participants. The methods used include counseling on the nutritional content and benefits of moringa leaves, as well as the direct practice of processing moringa leaves into food products such as sponge cakes and puddings. The results of the activities showed success which was marked by the enthusiasm and active participation of the community in the evaluation sessions and processing demonstrations. The community is able to answer evaluative questions well and show skills in processing moringa leaves independently. In addition to increasing knowledge, the community also shows a commitment to implementing the results of counseling in daily life, including in efforts to reduce high blood pressure through the consumption of processed moringa leaves. This activity ran smoothly and had a positive impact on improving nutrition literacy and public health. It is hoped that this activity can be a model of sustainable community empowerment based on local potential.